A Motivational Interviewing Intervention to Promote CRC Screening: A Pilot Study. Issue 1 (7th January 2022) - Adegboyega, Adebola; Aleshire, Mollie; Wiggins, Amanda T.; Palmer, Kelly; Hatcher, Jennifer
Abstract : Background: Appalachian Kentuckians suffer a disproportionate incidence and mortality from colorectal cancer (CRC) and are screened at lower rates (35%) compared with 47% of Kentuckians. Objective: The aim of this study was to evaluate the efficacy of a motivational interviewing intervention delivered by trained Lay Health Advisors on CRC screening. Method: Eligible participants recruited from an emergency department (ED) completed a baseline survey and were randomized to either the control or the motivational interviewing intervention provided by Lay Health Advisors. Follow-up surveys were administered 3 and 6 months after baseline. To evaluate potential differences in treatment and control groups, t tests, χ 2, and Mann-Whitney U tests were used. Results: At either the 3- or 6-month assessment, there was no difference in the CRC screening by group ( χ 2 = 0.13, P = .72). There was a significant main effect for the study group in the susceptibility to CRC model; regardless of time, those in the intervention group reported approximately 1-point higher perceived susceptibility to CRC, compared with controls (est. b = 0.68, P = .038). Age and financial adequacy had a significant effect related to CRC screening. Older participants (est. b = 0.09, P = .014) and those who reported financial inadequacy (est. b = 2.34, P = .002) reported more screening barriers. Conclusion: This pilot study elucidated important factors influencing the uptake of CRC for an ED transient population and this may be useful in the design of future interventions using motivational interviewing in EDs. Implications for Practice: Nurses can provide information about CRC screening guidelines and provide referrals to appropriate screening resources in the community.